RANCANG SISTEM PENDETEKSI HAMA PADA TANAMAN BERBASIS ARDUINO UNO - Soni Soni; Karnadi Karnadi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
To improve agricultural yields and reduce losses caused by pest attacks, this research designs a pest detection system for plants based on Arduino Uno. This system is designed to automatically detect the presence of pests using an ultrasonic sensor. The ultrasonic sensor functions as a detector for pest movements approaching the plants by identifying the frequency of sounds generated by pest movements. Additionally, a servo motor is used as a tool to repel pests detected by the ultrasonic sensor. The data is then transferred to an LCD via Arduino Uno, providing real-time information to farmers about pest attacks.System testing shows a pest detection accuracy of 80%, with an average response time of approximately 3 seconds. The results of this research are expected to provide a solution for farmers to monitor and control pest attacks, thereby increasing efficiency and enhancing productivity in agriculture.